Analisis Fluktuasi Hujan dan Morfologi Sungai terhadap Konsentrasi Banjir Daerah Surakarta - Alif Noor Anna; S Suharjo; Munawar Cholil (Universitas Muhammadiyah Surakarta, 2011)
This research aims to analyse rain fluctuation and river morphology to flood concentration in Bengawan Solo River, Surakarta. The method of this research is field survey supported by secondary data analysis. The survey was conducted using GPS (Global Positioning System). The result indicates that high intensity rainfall in the research area happened during October till April. River flow in dry season generally decreased in accordance with the distribution of low rainfall (dry month). Whereas, river flow rates seen to increase along with the rainfall that occurs in the rainy season. Other result show that point 11-18 (location in Tanjung village district of Sukoharjo till Semanggi village district of Pasar Kliwon) very superficial which became impact of the river. The point represent floods concentration, therefore if there is rain with high quantity, the water will rise and overflow to surface, especially point 11, 13, and 16 (Tanjung, Kedunggudel, and Telukan village district of Sukoharjo). The processes that occurred at these sites are sedimentation, and lateral erosion (horizontal erosion).